2015
DOI: 10.1002/acr.22542
|View full text |Cite
|
Sign up to set email alerts
|

Association of Socioeconomic Status With Treatment Delays, Disease Activity, Joint Damage, and Disability in Rheumatoid Arthritis

Abstract: Objective To examine the association of socioeconomic status (SES) and delays in DMARD treatment with clinical measures in rheumatoid arthritis (RA) patients. Methods RA patients were recruited from rheumatology clinics. We assessed SES based on education, occupation and income and divided patients into tertiles. The time from RA symptom onset to DMARD initiation (DMARD lag) was determined by self-report of the two dates, and distance to the rheumatologist (Distance) was obtained from Google Maps. We examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 35 publications
3
53
1
2
Order By: Relevance
“…When DAS28 was excluded from analysis, key aspects of its components (TJC, SJC and patient disease activity VAS) approached but did not independently reach statistical significance (data not shown). Relative socioeconomic disadvantage was additionally associated with longer patient delay in this study, similar to previous findings, despite universal healthcare access in Australia . Previous studies provide insight into how SES may impact health‐seeking behaviour, with low levels of health literacy affecting the ability of patients to assess appropriately new symptoms and seek help promptly .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…When DAS28 was excluded from analysis, key aspects of its components (TJC, SJC and patient disease activity VAS) approached but did not independently reach statistical significance (data not shown). Relative socioeconomic disadvantage was additionally associated with longer patient delay in this study, similar to previous findings, despite universal healthcare access in Australia . Previous studies provide insight into how SES may impact health‐seeking behaviour, with low levels of health literacy affecting the ability of patients to assess appropriately new symptoms and seek help promptly .…”
Section: Discussionsupporting
confidence: 84%
“…Relative socioeconomic disadvantage was additionally associated with longer patient delay in this study, similar to previous findings, despite universal healthcare access in Australia. 18,26 ACPA, anti-citrullinated peptide antibody; CRP, C-reactive protein; DAS28, 28-joint disease activity score; ESR, erythrocyte sedimentation rate; mHAQ, modified health assessment questionnaire; PGA, physician global assessment; RF, rheumatoid factor; SD, standard deviation; SJC, swollen joint count; TJC, tender joint count, VAS, visual analogue score. Previous studies provide insight into how SES may impact health-seeking behaviour, with low levels of health literacy affecting the ability of patients to assess appropriately new symptoms and seek help promptly.…”
Section: Patient Delaymentioning
confidence: 99%
“…This differences might be explained that certain patients with comorbidities were excluded in this study. Additionally, it is well known that SES is multifactor (e.g., education, income) and low SES could result in joint destruction in RA patients [9]. Our study also demonstrated that there were significant correlation between low education level and hand joint destruction.…”
Section: Discussionsupporting
confidence: 73%
“…While this is more than the recommended 12 weeks, it compares favorably with other early arthritis cohorts in developed countries and is much shorter than that reported in developing countries . Previous studies have suggested lower socioeconomic status (SES), lower number of swollen joints, seropositivity and presence of other comorbid conditions such as fibromyalgia and osteoarthritis to be associated with delayed presentation . In our study, education level and being non‐English speaking were used as surrogates for SES; however, these were not associated with increased delay to DMARD prescription.…”
Section: Discussionmentioning
confidence: 47%